2013
DOI: 10.1016/j.virol.2012.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a replication-competent chimeric simian-human immunodeficiency virus carrying env from subtype C clinical isolate through intracellular homologous recombination

Abstract: A new simian-human immunodeficiency virus (SHIV), carrying env from an uncloned HIV-1 subtype C clinical isolate (97ZA012), was generated through intracellular homologous recombination, a DNA repair mechanism of the host cell. PCR fragments amplified from an existing SHIV plasmid (a 7-kb fragment from the 5' end and a 1.5-kb fragment from the 3' end) and a 4-kb fragment amplified from 97ZA012 cDNA containing env were co-transfected to human lymphoid cells. The resulting recombinant was subjected to serial pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Although some SHIVs indeed induce AIDS in macaques, accumulating evidences have demonstrated that the genuine CCR5-tropism of input viruses is prerequisite for superimposing the experimental outcome on the natural disease progression in humans (Feinberg and Moore, 2002; Margolis and Shattock, 2006). Therefore, a number of CCR5-tropic SHIVs currently have been generated and utilized for in vivo macaque experiments (Hsu et al, 2003; Humbert et al, 2008; Nishimura et al, 2010; Fujita et al, 2012). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some SHIVs indeed induce AIDS in macaques, accumulating evidences have demonstrated that the genuine CCR5-tropism of input viruses is prerequisite for superimposing the experimental outcome on the natural disease progression in humans (Feinberg and Moore, 2002; Margolis and Shattock, 2006). Therefore, a number of CCR5-tropic SHIVs currently have been generated and utilized for in vivo macaque experiments (Hsu et al, 2003; Humbert et al, 2008; Nishimura et al, 2010; Fujita et al, 2012). …”
mentioning
confidence: 99%
“…Extensive search for appropriate Env sequences to confer CCR5-tropism and high replication-ability on HIV-1mt clones is required for our final purpose, i.e., the generation of proviral clones virologically similar to viruses of the SIVmac group that are pathogenic for macaques. In this regard, it is tempting to use “intracellular homologous recombination” as a measure to readily generate recombinant HIV-1 clones (Fujita et al, 2012). …”
mentioning
confidence: 99%
“…Regions with high env-diversity could also play a role in autologous immune escape, which has been substantially documented in HIV-1 [15,39]. Despite the formidable challenge of designing vaccines targeting variable regions in env, it is nevertheless of great importance that we continue to attempt this, in order to be able to target the hypervariable regions and wider epitopes from the diverse quasispecies that may exist in viral stocks [40,41]. Here we adopted a recombinant PCR method based on a dominance-based amplification rationale in pooled variants and microvariants of the viral population to mimic the vaccine diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that CXCR4-tropic SHIV decreased peripheral CD4+ T cells, and that CCR5-tropic SHIV decreased intestinal CD4+ T cells (Harouse et al, 1999; Ho et al, 2005). SHIV-KS661 and -KS705 have essentially the same env gene and use predominantly CXCR4 as a co-receptor for virus entry (Matsuda et al, 2010; Fujita et al, 2013). However, SHIV-KS661 decreased CD4+ T cells in systemic and mucosal immune tissues during primary infection (Miyake et al, 2006).…”
Section: Discussionmentioning
confidence: 99%